Chrysin ameliorates STZ-induced diabetes in rats: possible impact of modulation of TLR4/NF-κβ pathway - Abeer Salama; Gihan F Asaad; Aya Shaheen (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Growing evidence advocates that upregulation of toll-like receptor 4 (TLR4) has been suggested as a causative influence in the development and complications of diabetes mellitus. We aimed to study the antidiabetic activity of chrysin against streptozotocin (STZ)-induced diabetes via down-regulation of TLR4/nuclear factor (NF-κβ)/heat shock protein 70 (HSP70) pathway as well as modulation of clusters of differentiation 4 (CD4+) in rats. Experimental approach: Fifty rats were divided into five groups (n = 10). Group I, normal rats received a single intraperitoneal injection of buffer citrate; group II, STZ-induced diabetic rats; groups III-V, diabetic rats received glimepiride (0.5 mg/kg; p.o.) or chrysin (40 and 80 mg/kg; p.o.) respectively, for 10 days. Serum samples were extracted to determine nitric oxide (NO), malondialdehyde (MDA), and reduced glutathione (GSH), insulin, CD4+, TLR4, and NF-κβ. Pancreatic tissue samples were extracted to determine glucose transporter 2 (GLUT2). Part of the pancreas was kept in formalin for pathological studies. Findings/Results: An elevation in blood glucose, NO, and MDA serum levels and a reduction of pancreatic GLUT2 content, insulin, and GSH serum levels were observed in diabetic rats. STZ injection, also, showed an increase in serum TLR4, NF-κβ, and HSP70 levels and a reduction in serum CD4+ levels with pancreatic cells necrosis. These biochemical and histological changes were reversed in glimepiride and chrysin groups. Conclusion and implications: The present study proved that chrysin has a potent anti-diabetic effect through the elevation of insulin and GLUT2 levels, the reduction of oxidative stress, and the inflammatory pathways TLR4/NF-κβ/HSP70 with the regulation of CD4+.